Chronic demyelination exacerbates neuroaxonal loss in patients with MS with unilateral optic neuritis. Issue 3 (May 2020) - You, Yuyi; Barnett, Michael H.; Yiannikas, Con; Parratt, John; Matthews, Jim; Graham, Stuart L.; Klistorner, Alexander
Abstract : Objective: To examine the effect of chronic demyelination in the optic nerve of patients with MS on progressive loss of retinal ganglion cell (RGC) axons. Methods: Progressive retinal nerve fiber layer (RNFL) loss, as measured by optical coherence tomography, was longitudinally examined in 51 patients with MS with a history of unilateral optic neuritis (ON) and 25 normal controls. Patients were examined annually with a median of 4-year follow-up. Pairwise intereye comparison was performed between ON and fellow non-ON (NON) eyes of patients with MS using the linear mixed-effects model and survival analysis. The latency asymmetry of multifocal visual evoked potential (mfVEP) was used to determine the level of demyelination in the optic nerve. Results: Although both ON and NON eyes demonstrate significantly faster loss of RGC axons compared with normal subjects, ON eyes with severe chronic demyelination show accelerated thinning in the RNFL in the temporal sector of the optic disc (temporal RNFL [tRNFL]) compared with fellow eyes (evidenced by both the linear mixed-effects model and survival analysis). Furthermore, progressive tRNFL thinning is associated with the degree of optic nerve demyelination and reflects the topography of pathology in the optic nerve. More rapid axonal loss in ON eyes is also functionally evidenced by mfVEP amplitude reduction, which correlates with the level of optic nerve demyelination. Conclusions: Although the effect of demyelination on axonal survival has been demonstrated in experimental studies, our results provide first clinically meaningful evidence that chronic demyelination is associated with progressive axonal loss in human MS.